The corpse in the closet [large type] - Score, Lucy (Score, Lucy. Riley Thorn novels, 2025)
"Summer is heating up for reluctant psychic Riley Thorn and her handsome private investigator boyfriend, Nick Santiago. First, her disapproving grandmother arrives determined to make Riley take her powers seriously or face the wrath of "the Guild." Then there's the homicide detective who needs her help figuring out who murdered the well-dressed corpse in the walk-in closet. Nick's got his own hands full with a tricky missing-person case and his parents-who want to know why he didn't tell them about his live-in girlfriend. Then there's the fact that he's still the tiniest bit stressed about Riley almost getting murdered earlier that summer. Things go from bad to worse when the body count starts stacking up, the meet-the-parents dinner goes horribly wrong, and their elderly roommate is up to no good ... dressed like a mime. To top it off, Riley is forced to return to Channel 50 on official police business to question her spray-tanned news-anchor ex-husband and his new weather-girl fiancée. The trouble comes to a head when Riley receives a warning from the killer: Back off or she's next. Someone has to solve these murders before she becomes the next corpse."--